Draft Eleventh Five Year Plan (2007-2012) and Annual Plan 2007-2008 Government of Arunachal Pradesh - Planning Commission (Planning Commission, 2007)
Arunachal Pradesh still remains an underdeveloped State with a traditional economy. the State continues to be in the lowest quartile in terms of major indicators like literacy, per capita income etc. A large portion of population suffers from deprivation in matters of health, water supply etc. Even after more than 56 years of economic planning, the country has so far not been able to address adequately the specific requirements of Arunachal Pradesh. the impact of economic planning is neither impressive nor is there any visible impact of economic liberalization.
Government of Arunachal Pradesh, Department of Planning